Speculative orientation and tracking system - Ramos, João Ricardo Martins (2015)
The current progresses at the intersection of computer science and health care have the potential of greatly improving the living conditions of people with disabilities by removing obstacles that impair the normal unfolding of their everyday lives. Assistive technologies, as an application of scientific knowledge, aim to help users with their diminished capacities and, usually, imply a small adaptation from individuals so that they can use the devices that convey assistive functionalities. One of the most commonly diminished capabilities is that of spatial orientation. This is mirrored by several research works whose goal is to help human beings to travel between locations. Once set up, most of the systems featured in these research works requires changes in the configurations to be made manually in order to achieve a better adjustment to the user. In order to overcome this drawback, the work presented herein features a framework of Speculative Computation to set up the computation of the next step of a user using default values. The consequence of the application of the framework is a faster reaction to user stimuli, which may result in issuing warnings when he is likely to choose the wrong direction.